(untitled) (Ciencias Económicas, 2024)
Food security is currently, and has been for a long time, a globally concerning challenge. This issue is usually associated with food scarcity; however, its roots and implications are much broader and complex. Despite being recognized as a fundamental human right, its fulfillment remains an unresolved problem in many regions, especially in developing countries like ours. Addressing this matter involves reflecting on food supply and distribution, economic and social factors, inequality in access to resources, production systems, cultural aspects, inadequate policies and regulations, and the impact of the ecological crisis, among many others. This means that studying this problem requires both acknowledging the multiplicity of facets involved and striving to develop a comprehensive and multidimensional perspective. This article aims to explore the social and political aspects of food security. By doing so, the objective of this work was to contribute to understanding the issue of food security at a local and national level, considering its multidimensionality. To achieve this, a brief historical overview of the definition of food security was provided, the current state of the matter was reconstructed based on statistics concerning the food conditions of the global and local population, and finally, reflections were made on the existing production models and the government’s actions in addressing this scourge.